2010, No. 6, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Birutė Visokavičienė, The role of the monetary policy during the global financial crisis (2008-2009), 7 Valerija Gerikienė, Ramunė Kugaudaitė, Problems of the application of theoretical wage models, 19 Rusak Olga Arkadievna, The accounting aspects of the insurance transactions problem, 40 Kristina Rudžionienė, Aušra Morkevičienė, The conservatism principle in accounting: case of Lithuania, 50 Giedrė Laurinavičienė, Comparative analysis of income statements formed according to 1st IAS „Presentation of financial statements“, 3rd BAS „Income statement“ and the Fourth directive, 60 Jolita Jarmalaitė, Comparative analysis of inventory accounting following 2nd IAS „Inventories“ and 9th BAS „Inventories“, 71 Vaclovas Lakis, Giedrė Damaševičiūtė, The factors affecting relationships of internal auditors and auditees , 82 Vladislav Tomaševič, Efficiency analysis and evaluation of investment projects, 95 Nijolė Pakalnienė, Sufficiency of professional competence of graduates of Utena college accounting program for practical activity, 105 Jonas Mackevičius, Company internal control system: original researches, new thoughts, 114